Interpreting Magnolia through Badiou’s Axiomatic Judgment: The Visitation of the Idea that Humanity is Love (Itinera, 2023)
Alain Badiou’s interpretation of Paul Thomas Anderson’s film Magnolia is a paradigmatic example of his peculiar procedure of cinematic analysis called axiomatic judgment. According to the axiomatic judgment, to read a film is to inquire into the effects it has on thought. This essay reconstructs Badiou’s analysis of Magnolia to show how various cinematic elements—acting style, montage, music, and biblical references—are combined to arrange the visitation of a precise idea: that love is the fundamental precondition for humanity’s existence. Without love, the only experience of the world would be monadic. Examining Badiou’s interpretation of Magnolia does not simply aid our understanding of the film; it also clarifies Badiou’s theories of cinema and love.